Types of leisure-time physical activity participation in childhood and adolescence, and physical activity behaviours and health outcomes in adulthood: a systematic review - Kelcie Miller; Claire Morley; Brooklyn J. Fraser; Seana L. Gall; Verity Cleland (BMC, 2024)
Abstract Background Youth leisure-time physical activity participation benefits physical activity habits and health outcomes later in life. However, it is unknown if certain types of leisure-time physical activity contribute to these benefits in different ways; this knowledge could enhance public health efforts. This systematic review aimed to synthesise evidence of the longitudinal associations between childhood and adolescent leisure-time physical activity on adulthood physical activity behaviours and health outcomes. Methods A systematic search of the literature was conducted across five databases from inception to July 2022. English, peer-reviewed observational studies with a minimum of two timepoints of data collection were eligible for inclusion. We included studies that investigated the association between participation in leisure-time physical activity types in children and adolescents (i.e., 5-18 years), and physical activity, mental health, or cardiovascular outcomes in adulthood (i.e., ≥ 18 years). Results Fourteen studies were included in the review, totalling 34,388 observations across five countries. Running in adolescence was associated with increased adulthood physical activity in both sexes, while sports involvement was associated with an increase in physical activity in males only. Adolescent team sports participation was associated with reduced odds of early adulthood depression, with varying findings for anxiety disorders. There was preliminary evidence of minimum threshold requirements for participation in certain activities before associations with future physical activity or health outcome benefits were observed. Conclusions Preliminary findings suggest that the lifelong behavioural and health benefits of adolescent participation in leisure-time physical activity appear to be related to the type of activity undertaken, with potential differences between sexes. With the rarity of longitudinal studies spanning from childhood into adulthood, these findings provide important insights for public health strategies to optimise lifelong health and physical activity participation. Prospero registration CRD42022347792.